Mexico Financial Sector Assessment Program : Development Banks - World Bank Group; International Monetary Fund (World Bank, Washington, DC, 2017)
Several state owned financial institutions operating under different licenses provide credit as well as other financial services to virtually all market segments. State owned financial institutions (SOFIs) that provide credit in Mexico operate under different licenses including development banks, development agencies and development trusts. The 2013-2018 National Financing Plan (PRONAFIDE) stablishes ambitious lendingtargets for SOFIs with a view to foster financial deepening, resulting in a pro-cyclical creditbehavior.The Financial Reform of early 2014 sought to facilitate risk taking by DBs andimprove their operation to support the achievement of the PRONAFIDE targets.Currently, DBs support a third of all credit granted to the private sector, of whichabout 12 percent is first tier lending. DBs provide 19 percent of credit to the private sector bothdirectly in first-tier (12 percent) and through intermediaries (7 percent). In addition, DBs guarantee 12.6 percent of the credit provided by the banking system.Despite rapid credit growth, DBs have consistently shown sound asset quality and adequate levels of provisions.Profitability has recently declined as DBs have lowered loan rates to meet credit targets.Recent growth portfolio and declined profitability has put pressures in capitalizationratios in some of the largest DBs, however management of the capital with a groupperspective has resulted in capital reallocations among DBs to preserve ratios above 12percent.Currently, DB operations do not appear to pose mayor fiscal or financial stabilityrisks, but there are important concerns regarding the distortions and inefficiencies that thecurrent expansion of their operations could create. In addition to showing overall robustfinancial sector indicators, stress test conducted on the three largest DBs (Banobras, NAFIN andBancomext) showed their resilience to a variety of shocks. Mexican DBs aim at crowding-inprivate sector participation and thus they have substantial tier-II operations as well as guarantees. However, rapid expansion of their first tier lending poses concerns about crowding out while the introduction of several (albeit small in volume) programs with rate well below market levels raises concerns about financial additionally of their operations as well as sustainability of its financial inclusion efforts.